Integrasi Model Make A Match Berbasis Media Digital untuk Meningkatkan Minat Belajar Bahasan Himpunan - Hermanto, Hermanto; Ismiasih, Novi; Harliana, Harliana (Indo-MathEdu Intellectuals Journal, 2025)
This study employs the Classroom Action Research (CAR) method, conducted in one cycle. The researcher follows the cycle stages, which include pre-implementation, planning, classroom action execution, observation, and reflection, to assess the improvement in students' learning interest. The objective of this research is to determine whether the Make A Match model, supported by digital media, can enhance the learning interest of seventh-grade students at MTs Puspa Bangsa Cluring, consisting of 16 students, in the topic of sets. Data collection techniques utilized by the researcher include learning outcome tests with item validity testing, reliability testing of cognitive test results, differential power testing for each item, and difficulty testing for each question. Additionally, observations and field notes are conducted. The data analysis results indicate that mathematics instruction using the Make A Match model significantly improves students' learning interest, with mastery scores increasing from 31.25% (pre-test) to 87.5% (post-test). Furthermore, students' interest in learning, based on their activity levels, is assessed at 80.56%, categorized as good.